Changes in chemical profile of cephalic salivary glands of Scaptotrigona postica (Hymenoptera, Meliponini) workers are phase-related - Poiani, Silvana Beani [UNESP]; Morgan, E David; Drijfhout, Falko P.; Cruz-Landim, Carminda da [UNESP] (The Company of Biologists, 2015)
Most advanced eusocial bees recruit their nestmates to food resources. Recently, studies in Meliponini species showed that the cephalic salivary (labial) glands (CSGs) are responsible for the production of scent-trail pheromones. Studies on CSGs have shown changes in glandular cell morphology since the worker emerges from brood combs (newly emerged) till forager phase, which may be correlated to changes in the composition of secretion produced. However, no study has been made till now regarding to the composition of CSGs secretion of Scaptotrigona postica and the chemical changes that occur in this secretion according to the worker's life phase or tasks performed. In this study, the chemical profile of CSG secretion in S. postica workers was studied. Glands were taken from specimens newly emerged (NE), working in the brood combs area (CA) and forager (FO) and were analyzed by gas chromatography-mass spectrometry. The results showed that glandular secretion consists of oxygenated compounds of middle volatility (acids, alcohols, aldehydes, ketones, esters and ether), and their quantity varies among the different phases of life, increasing as the individual undergoes from intra- to extra-colonial activities. The NE phase contained the smallest variety and quantity of compounds. Due to the variability of compounds, the CA workers were separated into 3 groups according to the chemical constitution of their secretion. Forager workers showed the largest quantity and variety of chemical compounds. The major compounds in forager gland secretion are 7-hexadecen-1-yl acetate and 5-tetradecen-1-yl acetate. Statistical analysis indicates that the chemical composition of glandular secretion is task-related.